Efeito De Diferentes Níveis De Proteína E De Fibra Bruta Na Alimentação De Juvenis De Matrinxã, Brycon Cephalus - Pereira Filho, Manoel; Castagnolli, Newton; Storti Filho, Atilio; Pereira, Maria Inêz de Oliveira (Acta Amazonica, 1995)
The results of an experiment with matrinchã, Brycon cephalus,fed 9 diets, combined in 3 levels of protein (19, 25 e 31 %) and 3 levels of fiber (ca. 2, 10 and 20%), are shown. The final weight was positivelly influenced when fish fed higher levels of protein, but was not influenced by fiber levels. The higher levels of protein in the diet, increased protein content of carcass, and decreased the content of fat and ash, while fish fed the highest fiber levels assimilated more protein, had a higher percentage of ash and a lower fat content in the body composition. The results indicated that ingredients with high levels of fiber are well assimilated by matrinchã, increasing this way the range of agricultural by-products, normally rich in fiber, that could be used to formulate practical diets for this specie.
Protein and Crude Fiber Levels in the Diet of Juvenile Matrinxã, Brycon cephalus, an Amazonian Fish
Keywords: Matrinxã; Brycon Cephalus; Crude Protein; Crude Fiber; Matrinxã; Brycon Cephalus; Proteína Bruta; Fibra Bruta